Impact of dams on fish in the rivers of Nepal. (Metro Manila, Philippines Asian Development Bank, 2018)
This study was conducted by ADB to assess the impact of projects involving the construction of dams on aquatic biodiversity in Nepal.The findings may not be authoritative, but conclusions suggest that fish populations and the diversity of species are affected due to alterations in the ecosystem and blockage in life cycle movements.
Keywords: Fishes -- Effect of dams on; Dams -- Nepal; Electronic books